PERAN BADAN PERMUSYAWARATAN DESA DALAM PENGAWASAN DANA DESA - Eviandi Ibrahim (Ensiklopedia of Journal, 2023)
This research was conducted to analyze the role of the Village Consultative Body (BPD) in supervising the use of Village Funds in Kenagarian Gunung Malintang, Pangkalan Koto Baru District, Fifty City District. In this study the author uses an empirical juridical approach. The empirical juridical approach means that apart from looking directly at the review of people's understanding of the settlement of traffic accident cases, the author also looks directly at what is happening in the field. The results of this study are: In Nagari Gunuang Malintang Village Fund supervision is carried out by the village community, the Nagari Deliberation Board (Bamus), Government Internal Supervisory Apparatus (APIP), Camat, Financial Audit Board (BPK). In this thesis, the authors found problems with supervising village funds that occurred in the field, namely when village funds were used for development. In Nagari Gunung Malintang, Pangkalan Koto Baru District, the development that is meant is the construction of a nagari road. In this case the construction of the nagari road is supervised by the village head, village officials and each chief executive of the activity. In supervising village funds in Nagari Gunung Malintang, Pangkalan Koto Baru District, it has been running according to the applicable regulations, but there are several obstacles in its implementation. The inhibiting factors for supervising village funds in Nagari Gunung Malintang, Pangkalan Koto Baru District, are: Poor time management in carrying out supervision of Village Funds jointly by supervisors. Lack of human resources in preparing village fund reports by development implementers. And the lack of a place to inform reports on the use of village funds. Efforts made to overcome the inhibiting factors for supervising village funds are: coordinating with the team in carrying out supervision of village funds jointly by supervisors. Conduct technical guidance for preparing village fund reports. Organizing the creation of Nagari websites and information boards for everyone in Nagari Gunuang Malintang.Keywords: Supervision, Village Fund, Gunung Malintang District.